Free Field Construction of D-Branes in Rational Models of CFT and Gepner Models - Parkhomenko, S.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
This is a review article of my recent papers on free field construction of D-branes in N = 2 superconformal minimal models and Gepner models.